A highly conducting uniform sphere of thermal capacity C is heated by an electric heater, a resistance R fitted within the sphere. A constant current I is passed through the heater starting at time t = 0 which gives constant power . The sphere loses heat at a rate equal to k times the temperature difference between the sphere and the surrounding. The initial temperature of the sphere and that of the surrounding is 0 ° C .
The time at which sphere attains half of its maximum attainable temperature is k c ln 2 a . Then find the value of " a ".
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@NISHANT RAI pls make it O KELVIN ..
Curve proven related to exponential change from 0 towards arrival is a saturation to certain level as:
M (1 - e − c k t ) = 2 M of M (1 - 1) to M (1 - 0) of full time changes.
⇒ (1 - e − c k t ) = 2 1
⇒ 2 − 1 = e − c k t
⇒ e − L n 2 = e − c k t
⇒ Ln 2 = c k t
⇒ t = k c Ln 2
Therefore, a = 1
Answer: 1
Problem Loading...
Note Loading...
Set Loading...
Let thermal energy stored in the sphere be given by E , and the temperature of the sphere be T (which is also the temperature relative to the surroundings provided we remain in degrees Celsius). τ is the time required by the question.
The power input (energy per unit time) from resistor to sphere is given by I 2 R and the power loss from sphere to surroundings by k T
Hence the differential equation describing the situation is:
d t d E = I 2 R − k T
Now, using the heat capacity equation, E = C T ⇒ d t d E = C d t d T
Then substituting into the differential equation:
C d t d T = I 2 R − k T
The maximum attainable temperature is achieved when d t d E = 0
⇒ I 2 R = k T m a x ⇒ T m a x = k I 2 R
By separation of variables in the differential equation:
∫ 0 2 T m a x I 2 R − k T C d T = τ
⇒ τ = − k c ln ( I 2 R − k T ) ∣ ∣ ∣ 0 2 T m a x
⇒ τ = k c ln 2
∴ a = 1